Optimizing Access to Basic Ultrasound Screening and Improving Pregnant Women’s Knowledge in Bangun Rejo Village: Optimalisasi Aksesibilitas Skrining USG Dasar dan Peningkatan Pengetahuan Ibu Hamil di Desa Bangun Rejo - Kismiasih Adethia; Herna Rinayanti Manurung; Amelia Erawaty Siregar; Nurazizah Nurazizah; Sri Murtini; Suci Indah Lestari (Room of Civil Society Development, 2026)
Access to antenatal screening at the rural primary care level remains limited and may contribute to delayed identification of pregnancy-related abnormalities. This community service program aimed to support the optimization of access to basic ultrasound screening, facilitate initial antenatal assessment, and improve pregnant women’s knowledge in Bangun Rejo Village. A community-based evaluation using a one-group pre-test–post-test design involved all 26 eligible pregnant women through total sampling. The intervention integrated interactive maternal health education with free basic ultrasound examinations using a participatory clinical approach. Knowledge was assessed using a validated 30-item multiple-choice questionnaire administered before and immediately after the intervention. Basic ultrasound examinations identified cephalic presentation in 19 participants (73.1%) and breech or transverse presentation in 7 participants (26.9%) who were in the first or second trimester. All participants had adequate amniotic fluid volume and placental location in the uterine corpus; therefore, no abnormalities requiring immediate referral were identified in the assessed ultrasound parameters. The proportion of participants in the good knowledge category increased from 34.6% to 73.1%, while the poor category decreased from 42.3% to 3.8%. The Wilcoxon Signed-Rank Test indicated a significant difference in knowledge categories before and after the intervention (Z = −3.542; p < 0.001). The program facilitated access to basic ultrasound services during its implementation, supported initial antenatal screening, and improved participants’ short-term knowledge. Continued monitoring is required to assess knowledge retention, referral adherence, and pregnancy outcomes.